Column base joint made with ultrahigh-strength steel bars and steel tubular: An experimental study. (1st February 2021) - Mou, Ben; Zhou, Wanqiu; Qiao, Qiyun; Feng, Peng; Wu, Chenglong
Highlights: The seismic behavior of column base joint made with high strength steel was evaluated. Four column base joints with square and circular cross-sections and with 0 and 0.25 axial force ratios have been tested. The flexural capacity of the CFST column base joints are determined by the calculation formulae. Abstract: The use of ultrahigh-strength steel in civil, bridge, and offshore engineering is increasing rapidly. In this study, the seismic behavior of a concrete-filled steel tubular (CFST) column base joint with implanted ultrahigh-strength reinforcing bars has been investigated. The steel tubular and the implanted reinforcing bars are made of ultrahigh-strength steel. Four column base joints with square and circular cross-sections and with 0 and 0.25 axial force ratios have been tested to discuss the hysteretic capacity, deformation, ductility, failure modes, and energy dissipation. The axial force is the main parameter to improve the flexural capacity of the column base joints. Owing to the slip between the infilled concrete and the steel tubular columns, the hysteresis loops show an obvious pinch phenomenon. The tested specimens demonstrate good ductility behavior. Finally, the flexural capacity of the CFST column base joint has been determined by analyzing the failure characteristics and stress of the CFST columns. The flexural capacity of the CFST column base joints determined by the calculation formulae matches well with the test results. The ratio of the calculated and tested flexural capacity is between 0.967 and 1.059, and the absolute relative error is between 0.131% and 5.595%.